PERAN AUDITOR INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PERUSAHAAN - Alfah Rahmatul Yusnia; Liviana Dwi Rahmadhani, Regita Cahyani Febrianti, Ummatul Muthohharo, Yuni Sukandani (CV. ADIBA AISHA AMIRA, 2024)
This research is aimed at finding out the role of internal auditors on the quality of company financial reports. The purpose of this research is to analyze the role of internal auditors on the quality of financial reports in companies. This type of research is qualitative descriptive research. The data used is secondary data. The data collection methods in this research are documentation and literature review. Data analysis techniques use data reduction techniques, data interpretation, and drawing conclusions and data verification. Based on the test results using Data Reduction, 5 research journals were obtained that supported this research. The test results using data interpretation techniques showed that there were 3 research journals that were in line and 1 research journal that was not in line which supported the research. So overall, drawing conclusions and verification based on journals that support the variable role of internal auditors influences the quality of the company's financial reports, but the verification results need to be reviewed using data analysis techniques that are supported by strong evidence so that the credible conclusions can be proven using tests that support further research